Deutsche Eisenbahner! - Forster, Albert (1902-1952). (Danzig : [s.n.], 1939)
Odezwa Forstera do kolejarzy gdańskich z 1 września 1939 r.
Keywords: Wojna światowa (1939-1945) -- Polska -- Gdańsk; Gdańsk (Polska) -- 1900-1945 -- druki ulotne; Gdańsk (Polska) -- 1900-1945 -- źródła; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- druki ulotne; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- źródła